STUDENTS' INDEPENDENT THINKING: METHODOLOGICAL APPROACHES TO DEVELOPMENT (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the concept of fostering independent thinking among students through various methodological approaches. It highlights the importance of developing critical analysis, self-reflection, and problem-solving skills in an educational context. The piece discusses strategies such as inquiry- based learning, Socratic dialogue, reflective practices, collaborative learning, and the integration of autonomy and technology in teaching. It also examines challenges such as the limitations of traditional education systems and the need for gradual scaffolding to support students' transition toward self-directed learning. Concluding sections emphasize the transformative role of independent thinking in preparing students to become adaptable, creative, and responsible individuals capable of addressing the complexities of modern life. This article serves as a valuable resource for educators, policymakers, and stakeholders aiming to enhance teaching practices and empower learners.